Targeted genetic manipulations of neuronal subtypes using promoter-specific combinatorial AAVs in wild-type animals - Gompf, Heinrich S.; Budygin, Evgeny A.; Fuller, Patrick M.; Bass, Caroline E. (Frontiers in Behavioral Neuroscience, 2015)
Techniques to genetically manipulate the activity of defined neuronal subpopulations have been useful in elucidating function, however applicability to translational research beyond transgenic mice is limited. Subtype targeted transgene expression can be achieved using specific promoters, but often currently available promoters are either too large to package into many vectors, in particular adeno-associated virus (AAV), or do not drive expression at levels sufficient to alter behavior. To permit neuron subtype specific gene expression in wildtype animals, we developed a combinatorial AAV targeting system that drives, in combination, subtype specific Cre-recombinase expression with a strong but non-specific Cre-conditional transgene. Using this system we demonstrate that the tyrosine hydroxylase promoter (TH-Cre-AAV) restricted expression of channelrhodopsin-2 (EF1α-DIO-ChR2-mCherry-AAV) to the rat ventral tegmental area (VTA), or an activating DREADD (hSyn-DIO-hM3Dq-mCherry-AAV) to the rat locus coeruleus (LC). High expression levels were achieved in both regions. Immunohistochemistry (IHC) showed the majority of ChR2+ neurons (>93%) colocalized with TH in the VTA, and optical stimulation evoked striatal dopamine release. Activation of TH neurons in the LC produced sustained EEG and behavioral arousal. TH-specific hM3Dq expression in the LC was further compared with 1) a Cre construct driven by a strong but non-specific promoter (non-targeting), and 2) a retrogradely-transported WGA-Cre delivery mechanism (targeting a specific projection). IHC revealed that the area of c-fos activation after CNO treatment in the LC and peri-LC neurons appeared proportional to the resulting increase in wakefulness (non-targeted > targeted > ACC to LC projection restricted). Our dual AAV targeting system effectively overcomes the large size and weak activity barrier prevalent with many subtype specific promoters by functionally separating subtype specificity from promoter strength.